Precision cosmology from future lensed gravitational wave and electromagnetic signals - Kai Liao (Nature Portfolio, 2017)
Gravitational wave sources can be used as cosmological probes through a direct distance luminosity relation. Here, the authors demonstrate that the time delay between lensed gravitational wave signals and their electromagnetic counterparts can reduce the uncertainty in the Hubble constant.